The The Implementation of the Daily English Conversation (DEC) Program at Walisongo Islamic Boarding School - Fadila Nurmala Tsania; Dhinuk Puspita Kirana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to investigate the implementation of the Daily English Conversation (DEC) program and its role in improving students' speaking skills at the Walisongo Islamic boarding school. This study employed a qualitative approach, using a case study method. Data were collected through interviews and observations. This research involves 40 students from Class 4 of the Language Improvement Section (LIS), who actively participated in a daily English conversation program. The interview participants included several fourth-grade students of the LIS, serving as a purposively selected sample. Thematic analysis was used to analyze the data. The results showed that the program was implemented systematically through various activities, including vocabulary building, daily conversations, public speaking exercises, and activities such as Language for Fun and Morning Tea. The institutional structure involving student leaders supported the program. The habit of using English in daily life can improve vocabulary, fluency in speaking, and self-confidence. It can be concluded that this program is highly effective in improving students' speaking skills and can be applied in other boarding school educational institutions.